Mobilidade urbana na região metropolitana do Rio de Janeiro: um estudo dos últimos 50 anos à luz dos dias atuais - Azevedo, José Antônio Pérez Rojas Mariano de (2015)
The goal of this work is to analyze, from the perspective of public policies implemented in the last five decades, the urban mobility and the public transport in Rio de Janeiro Metropolitan Region. In other words, did the public transport politics, together with the concept of life quality, improved the fluminense citizen experience on the last five decades? How did the public power investments on the last years, as well as the ones that are scheduled for the future, affected and will affect people’s life? Based on that, interviews with public authorities and experts will be realized, besides literature review in official documents, academic articles and newspaper articles. On the first chapter, the methodology applied will be explained, as well as the question and the reasons that lead to the choice for the theme. On the second chapter, a holistic analysis about urban mobility is made, starting by its concept, going through historical context in Rio de Janeiro Metropolitan Region, the advantages and disadvantages of every sort of public transport and the current debates on the theme. On the third chapter, the interviews realized with managers and experts on the theme are reviewed. Lastly, on the conclusion, a model of urban mobility is proposed, thinking about the whole society.